Second order nonlinear Cauchy problems in a four dimensional space - A.Di Bartolomeo; Quartieri, J.; Steri, S. (Нелінійні коливання, 2003)
In this paper a general second order Cauchy problem in four dimensional space is considered and sufficient conditions for integrability with generalized Lie series method are determined.